Comparative analysis of gamification approaches in education - Ahmad Fuadi, Nur Faizura; Othman, Muhammad Fakri; Senan, Norhalina (Penerbit UTHM, 2017)
Games promised that when it comes to comparison between them with traditional training, they are more engaging and entertaining [1]. Using gamification has attracted many attentions from researchers [2] but empirical support of these tasks has been slowly emerge. Besides, games also offer multiple roles including storytelling, programming, artwork, sound and mechanics [3]. Every year, school will go through the list of children who get enrolled. There was never been a year without children with poor skills in Bahasa, English and Mathematics.